Design and implementing possibilities of composite pontoon bridge - Błażejewski, Wojciech; Filipiak, Adrianna; Barcikowski, Michał; Łagoda, Karolina; Stabla, Paweł; Lubecki, Marek; Stosiak, Michał; Śliwiński, Cezary; Kamyk, Zbigniew (Advances in Mechanical and Materials Engineering, 2018)
This work focuses on the analysis of actions conducted by the Military Institute of Engineer Technology and Wroclaw University of Science and Technology regarding the production and testing (on proving ground) of composite pontoon bridge. The starting point for this work was the experience gained from the project named „Light, resistant to environmental hazards, aluminum-composite hybrid pontoon used in constructing floating bridges of MLC 70/110 class”. Each one of the three V-shaped outriggers was designed using different technology. The middle part was constructed mostly of aluminum by company PREMO, but the smaller outrigger and all parts of the bow were made at Wroclaw University of Science and Technology from composite material reinforced with glass, aramid and carbon fibers. The inside was filled with multiple types of foam. During successful tests on proving grounds, conducted by Military Institute of Engineer Technology, elements were connected with PP-64 pontoons. It was proven that Wroclaw scientific society is capable of designing and manufacturing of a prototype pontoon bridge park.